2021
DOI: 10.1371/journal.pone.0253842
|View full text |Cite
|
Sign up to set email alerts
|

The role of procalcitonin and presepsin in the septic febrile neutropenia in acute leukemia patients

Abstract: Background The source of bacterial infection in neutropenic acute leukemia patients is detected in about 20–30% of cases. Bacterial cultures may require a long incubation period and risk false-positive and false- negative results. Therefore, biomarkers distinguishing septic febrile neutropenia from other etiologies in acute leukemia patients play the important role in patient assessment and treatment planning. This study aims to determine the role of procalcitonin (PCT) and presepsin (PSPN) in infectious compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
1
4
1
Order By: Relevance
“…Among the cells that are thought to contribute to the production of presepsin, hepatocytes seem the most plausible hypothesis, together with resident monocytes and tissue macrophages [32][33][34] 34,38 . As in other in vivo studies, but differently from in vitro studies, we did not find a difference between presepsin levels in patients with a Gram-negative or a Gram-positive bacteremia, suggesting that it is equally released in presence of LPS and in presence of other ligands typical of Gram-positive bacteria 31,34,35,39,41 . Presepsin did not reveal to be a useful biomarker in the prediction of bacteremia, neither at T0 nor at T1, showing only at T1 a good sensitivity (0.90) and PPV (0.90) when a 213 pg/mL cut-off is used.…”
Section: Discussioncontrasting
confidence: 50%
“…Among the cells that are thought to contribute to the production of presepsin, hepatocytes seem the most plausible hypothesis, together with resident monocytes and tissue macrophages [32][33][34] 34,38 . As in other in vivo studies, but differently from in vitro studies, we did not find a difference between presepsin levels in patients with a Gram-negative or a Gram-positive bacteremia, suggesting that it is equally released in presence of LPS and in presence of other ligands typical of Gram-positive bacteria 31,34,35,39,41 . Presepsin did not reveal to be a useful biomarker in the prediction of bacteremia, neither at T0 nor at T1, showing only at T1 a good sensitivity (0.90) and PPV (0.90) when a 213 pg/mL cut-off is used.…”
Section: Discussioncontrasting
confidence: 50%
“…Our results showed no significant difference in PCT levels at T0, the time immediately after surgery, between group NS and group PS under non-AKI and mild-AKI groups. PCT is released from C-cells of the parathyroid gland in normal circumstances, and pro-inflammatory cytokines, such as TNF- α and IL-6, increase its release from neuroendocrine cells in lungs or intestine [ 22 , 23 ]. Accordingly, PCT may be elevated not only by infection, but also by other sources of inflammation, such as trauma or a surgical procedure [ 5 , 9 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the increase in procalcitonin in patients with sepsis and SIRS (Mustafić et al 2018 ; Patil and Patil 2020 ; Sharma et al 2020 ). The increased bacterial infection leads to increased procalcitonin (Moustafa et al 2021 ). However, the serum concentration of procalcitonin has not been evaluated in dogs with SIRS in the intensive care unit.…”
Section: Discussionmentioning
confidence: 99%